Pengaruh Tekanan Kempa Terhadap Keteguhan Lengkung Statis Pada Sambungan Menjari Kayu Meranti Merah (Shorea sp.) Dengan Perekat Polivinil Asetat (PVAc) - DAYADI, IRVIN (PERENNIAL, 2024)
The joint of glued laminated wood with adhesive is widely used and affects the static bending strength value in its use. The compression pressure is one of the critical factors in the gluing of joints. This research aims to determine the effect of variations in compression pressure on the static bending strength of finger-jointed red meranti (Shorea sp.) wood glued with an exterior type of polyvinyl acetate (PVAc) adhesive in Synteco brand. The static bending strength testing referred to the German standard DIN (Deutsches Intitut fur Normung) DIN 52186-78. The data from 3 treatments of compressive pressure variations (2 bar, 2.5 bar, and 3 bar) were analyzed for variation in a completely randomized design (CRD) with 20 replications. The research results showed that the highest static bending strength of finger-jointed Shorea sp. was found at a compression pressure of 3 bar (P3), in which its modulus of elasticity (MoE) was 9,975.53 N/mm2 and the modulus of rupture (MoR) was 60.77 N/mm2. The MoE and MoR of the finger-jointed wood were still lower than its control (without joints), in which MoE was 10,017.07 N/mm2 and MoR was 82.07 N/mm2.